The Effect of the School Literacy Movement on the Reading Interest and Reading Motivation of Second-Grade Elementary School Students - Yayang Mai Zura; Siti Quratul Ain (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effect of the School Literacy Movement (SLM) on the reading interest and reading motivation of second-grade students at SDN 115 Pekanbaru. The research employed a quantitative approach using an ex post facto design. The study population consisted of all 110 second-grade students at SDN 115 Pekanbaru. A sample of 27 students was selected through purposive sampling, with Class IIC chosen as the research subject because it exhibited relatively low levels of reading interest and reading motivation. Data were collected using a questionnaire that had been tested for content validity, construct validity, and reliability. Prior to hypothesis testing, prerequisite analyses, including normality and linearity tests, were conducted. The hypotheses were tested using simple linear regression analysis. The results revealed that the School Literacy Movement had a positive and significant effect on students' reading interest, with a significance value of 0.048 (< 0.05) and a coefficient of determination (R²) of 0.147, indicating that the program accounted for 14.7% of the variance in reading interest. Furthermore, the School Literacy Movement also had a positive and significant effect on students' reading motivation, with a significance value of 0.002 (< 0.05) and an R² value of 0.330, indicating that it explained 33.0% of the variance in reading motivation. These findings demonstrate that the implementation of the School Literacy Movement contributes to improving students' reading interest and motivation. Therefore, the School Literacy Movement can serve as an effective strategy for fostering a reading culture and enhancing literacy outcomes among elementary school students.